Reading skill builders for college Spanish a preliminary study - Lopez, Francisco F. 1920- (s.n.], 1963)
Reading skill builders for college Spanish is constructed in this study and is subdivided into the following: the practices and trends in the teaching of Spanish, the skill builders that may help in the teaching of Spanish and the results of a try-out sample construction of a reading skill builder.